ARRDC3 suppresses breast cancer progression by negatively regulating integrin β4 - Draheim, K M (Nature Publishing Group, 2010)
Large-scale genetic analyses of human tumor samples have been used to identify novel oncogenes, tumor suppressors and prognostic factors, but the functions and molecular interactions of many individual genes have not been determined. In this study we examined the cellular effects and molecular mechanism of the arrestin family member, ARRDC3, a gene preferentially lost in a subset of breast cancers. Oncomine data revealed that the expression of ARRDC3 decreases with tumor grade, metastases and recurrences. ARRDC3 overexpression represses cancer cell proliferation, migration, invasion, growth in soft agar and in vivo tumorigenicity, whereas downregulation of ARRCD3 has the opposite effects. Mechanistic studies showed that ARRDC3 functions in a novel regulatory pathway that controls the cell surface adhesion molecule, β-4 integrin (ITGβ4), a protein associated with aggressive tumor behavior. Our data indicates ARRDC3 directly binds to a phosphorylated form of ITGβ4 leading to its internalization, ubiquitination and ultimate degradation. The results identify the ARRCD3-ITGβ4 pathway as a new therapeutic target in breast cancer and show the importance of connecting genetic arrays with mechanistic studies in the search for new treatments.